2013
DOI: 10.5539/jas.v5n9p65
|View full text |Cite
|
Sign up to set email alerts
|

Potato (Solanum tuberosum L.) and Bean (Phaseolus vulgaris L.) in Sole Intercropping: Effects on Light Interception and Radiation Use Efficiency

Abstract: An investigation was carried out during three crop growing seasons (2005; 2006 and 2007) at the Technical Center of Potato (CTP) situated in the low valley of Medjerda river at Saida (Tunisia) to find out how potato and bean can grow and develop in an intercropping system rather than in sole cropping. Crop productivity of potato and bean intercropping systems was evaluated in terms of total dry matter production. The light interception and radiation use efficiency by this system were calculated in sole croppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
3
10
1
Order By: Relevance
“…In this study, TDM accumulation was positively related to interception of PAR ( Figure. 4), which is a finding in line with the results reported by other researchers (Li et al, 2009;Miranzadeh et al, 2011, Rezig et al, 2013a, 2013b. Miralles and Slafer (1997) indicated that post-anthesis RUE appeared to be closely and positively associated with the number of grains set per unit biomass at anthesis in winter wheat.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, TDM accumulation was positively related to interception of PAR ( Figure. 4), which is a finding in line with the results reported by other researchers (Li et al, 2009;Miranzadeh et al, 2011, Rezig et al, 2013a, 2013b. Miralles and Slafer (1997) indicated that post-anthesis RUE appeared to be closely and positively associated with the number of grains set per unit biomass at anthesis in winter wheat.…”
Section: Discussionsupporting
confidence: 82%
“…Equally, different crops have been found to be closely correlated with cumulative radiation intercepted by their foliage e.g. Sulla (Rezig et al, 2013b), green been (Rezig et al, 2010(Rezig et al, , 2013a and potato (Rezig et al, 2010(Rezig et al, , 2013a(Rezig et al, , 2013b …”
Section: Discussionmentioning
confidence: 99%
“…Our results showed clearly that under drought stress predominantly in the two treatments (D 3 = 40 % ETc and D 4 = pluvial), TDM and PAR abs decreased significantly with deficit irrigation.This result was consistent with the findings of Tesfaye et al (2006), they found that the dry matter production is linearly related to PAR interception and they reclaimed that the low TDM production in the MS treatment (Mid-season stress=Flowering/pod setting) is principally attributed to low PAR interception. In fact, irrigation is important factor for plant productivity which plays vital role in biomass accumulation, dry matter partitioning and grain development (Hasanuzzaman and Karim 2007;Hasanuzzaman et al, 2008).There is a linear relationship between cumulative-intercepted photosynthetically active radiation (PAR abs) and accumulated-biomass (Loomis and Williams, 1963;Monteith, 1972;1977;Gallagher and Biscoe, 1978;Kiniry et al, 1989;Russell et al, 1989;Sinclair and Muchow, 1999;Ceotto and Castelli, 2002;Rezig et al, 2013a;2013b;. Therefore, determining RUE is an important approach for understanding crop growth and yield (Sinclair and Muchow, 1999).Results in table 1 showed that the radiation use efficiency (RUE) decreased with deficit irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…The soil had a clay-loam texture with 180 mm m-1 total available water and 2 g l -1 water salinity. The bulk density varies from 1.34 to 1.60 from the surface to the depth (Rezig et al, 2013a).…”
Section: Materials and Methods Experimental Sitementioning
confidence: 99%